2002
DOI: 10.1038/sj.leu.2402444
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating critical mechanisms of deregulated stem cell turnover in the chronic phase of chronic myeloid leukemia

Abstract: Chronic myeloid leukemia (CML) has been studied intensively for many years; yet its treatment remains problematic and its biology remains elusive. In chronic phase, the leukemic clone appears to be maintained by a small number of BCR-ABL-positive hematopoietic stem cells that differentiate normally and amplify slowly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 90 publications
7
93
0
Order By: Relevance
“…First, the fusion genes must allow for the production of functional FTKs; several of those detected in normal leukocytes have an aberrant structure owing to wrong junctions between BCR and ABL exons or to the insertion of intervening sequences . Second, FTKs may not reflect incipient leukemias, because they were generated in relatively mature progenitors from which the derived clones are eventually lost through normal cell differentiation and death; only those formed in leukemia stem cells may produce malignancies (Holyoake et al, 1999). Third, FTK-positive cells may need to acquire additional genetic and/or epigenetic changes before becoming tumorigenic (Shteper and Ben-Yehuda, 2001).…”
Section: Additional Factorsmentioning
confidence: 99%
“…First, the fusion genes must allow for the production of functional FTKs; several of those detected in normal leukocytes have an aberrant structure owing to wrong junctions between BCR and ABL exons or to the insertion of intervening sequences . Second, FTKs may not reflect incipient leukemias, because they were generated in relatively mature progenitors from which the derived clones are eventually lost through normal cell differentiation and death; only those formed in leukemia stem cells may produce malignancies (Holyoake et al, 1999). Third, FTK-positive cells may need to acquire additional genetic and/or epigenetic changes before becoming tumorigenic (Shteper and Ben-Yehuda, 2001).…”
Section: Additional Factorsmentioning
confidence: 99%
“…In normal adult marrow, where the vast majority of the most primitive hematopoietic cells are located, almost all of these are quiescent and hence are not immediately affected by short term treatments. 72 In contrast, successively later stages of differentiation, identified as the cells that produce progressively smaller colonies, show a correspondingly progressive increase in the proportion of their members that are already proliferating in vivo. Thus, by the time hematopoietic cells normally begin to be morphologically identifiable, all appear to be proliferating and the onus for compartment control normally shifts to an almost exclusive reliance on mechanisms that control apoptosis.…”
Section: Altered Proliferation Controlmentioning
confidence: 99%
“…However, recent studies by Graham et al (2002) have suggested that imatinib is not cytotoxic to the CML stem cell population, but rather only cytostatic. A large proportion of CML stem cells are quiescent (Holyoake et al, 1999), suggesting that constitutive kinase activity is necessary for survival of actively cycling CML cells, but perhaps not for quiescent or less metabolically active CML stem cells. Further, anecdotal evidence from clinical experience indicates that CML is effectively suppressed as long as patients continue to take imatinib, but that relapse occurs when treatment is discontinued.…”
Section: Molecular Mechanisms Controlling Growth and Survival Of Lscmentioning
confidence: 99%
“…In attempting to understand how genetic instability or mutations might affect the stem cell pool, an important observation to consider is that LSC maintain a largely quiescent cell cycle status (Holyoake et al, 1999;Guzman et al, 2001a;Guan et al, 2003). Therefore, mutations that affect genomic stability will typically only manifest themselves in the small percentage of cycling cells.…”
Section: Self-renewal and Stem Cell Pathogenesismentioning
confidence: 99%